Proceedings of Fifth Doctoral Symposium on Computational Intelligence DoSCI 2024, Volume 1 - Swaroop, Abhishek; Kansal, Vineet; Fortino, Giancarlo; Hassanien, Aboul Ella.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This book features high-quality research papers presented at Fifth Doctoral Symposium on Computational Intelligence (DoSCI 2024), jointly organised by Institute of Engineering & Technology, Lucknow, India, and School of Open Learning, University of Delhi in association with University of Calabria, Italy, on May 10, 2024. This book discusses the topics such as computational intelligence, artificial intelligence, deep learning, evolutionary algorithms, swarm intelligence, fuzzy sets and vague sets, rough set theoretic approaches, quantum-inspired computational intelligence, hybrid computational intelligence, machine learning, computer vision, soft computing, distributed computing, parallel and grid computing, cloud computing, high-performance computing, biomedical computing, and decision support and decision making.
Keywords: Computational intelligence; Artificial intelligence; Data structures (Computer science).; Information theory; Computational Intelligence; Artificial Intelligence; Data Structures and Information Theory